Annual Dynamics of Winery Wastewater Volumes and Quality and the Impact of Disposal on Poorly Drained Duplex Soils - Mulidzi, A.R.; Clarke, C.E.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2018)
The composition and volume of winery wastewater change throughout the year. Quality is usually at its worst when vintage operations are dominated by the production of red wines. The objective of this study was to investigate the annual dynamics of winery wastewater volumes and quality, as well as the effect of winery wastewater irrigation on the chemical soil properties of a poorly drained duplex soil. The study was conducted over two and half years. The wastewater contained a high concentration of potassium (K+) and low levels of sodium (Na+). The results of the study confirmed that winery wastewater did not comply with South African national legislation for wastewater irrigation with regard to chemical oxygen demand (COD) and pH throughout the study period, while some prominent spikes were observed in sodium adsorption ratio (SAR) and electrical conductivity (EC). Land application of winery wastewater resulted in the accumulation of high levels of K+ in the soil. It is important to note that this study represents the worst-case scenario, i.e. large amounts of wastewater were disposed of on a small surface, particularly during harvest and in winter. Due to the high volumes of wastewater irrigation plus rainfall, the inevitable over-irrigation leached large amounts of K+ beyond 90 cm soil depth. Unfortunately, the leached elements are bound to end up in natural water resources, resulting in the pollution of the environment.